Transport infrastructure investments and competition for FDI - Kate Hynes; Jie Ma; Cheng Yuan (University College Dublin, UCD School of Economics, 2017)
This paper studies how transport infrastructure investments affect a bidding war for a firm between two asymmetric countries within a region in a context of imperfect competition, where transport infrastructure investments play the role of a global public good, leading to a reduction in the unit trade cost between the two countries. A number of interesting results are derived from the model. In particular, transport infrastructure investments can intensify fiscal competition between the two countries. Surprisingly, this conventional wisdom seems to be confirmed by this paper for the first time. Welfare implications of the model are also examined.
Keywords: F21; F23; H40; 330; transport infrastructure investments; fiscal competition; FDI; imperfectly competitive market